O rosário macabro dos trabalhadores rurais: violência e resistência no Governo Sarney – a República envelhecida (1985 – 1989) - Mendes, Alberto Rafael Ribeiro (2023)
The first civilian government after the military dictatorship in Brazil, led by President JosÈ Sarney, represented, for rural workers, the intensification of all forms of violence in the countryside. The self-proclaimed “New Republic” was not able to break the bonds with the old authoritarian order, reproducing political measures and benefiting old partners; it did not carry out the proposal for agrarian reform announced by PNRA and was also unable to guarantee the protection of human rights in the countryside. This dissertation analyzes the role of the Comiss„o Pastoral da Terra (Pastoral Land Commission) – CPT (1975) and the Movimento dos Trabalhadores Rurais Sem Terra (Landless Rural Workers Movement) – MST (1984) in the work of producing visibilities and sayings about the problem of violence in the countryside, constituting what we call struggles to be able to voice the agony of rural workers and their allies in the struggle for land. It is intended to analyze the macabre Rosary, namely, the strategies and tactics of the MST and CPT to name, narrate, publish and denounce persistent violence, making it a matter of national order. Therefore, the analysis of the bulletins, training booklets, dossiers, newspapers, posters, and political cartoons, which serve as sources for this work, also takes them as tools for building the discourse on violence and instruments of the struggle and discursive battle in question, which complements that struggle on the land's ground, through occupation, settlements, and marches. Likewise, it is interesting to analyze how this discursive production centered on the persistence of violence was mobilized to highlight the similarities between the “old” militarized order and the establishment of a “new” Republic, which leads workers and mediation agents to perceive it as an aged Republic. What this dissertation demonstrates is the non-fulfillment of the new time, but the repetition of a land policy focused on the interests of the large estate and rural businessmen, in the same way that it continues to treat the struggles for agrarian reform and land as dangerous actions, as well as considering enemies all those who have joined the poor of the land, seen as conflict creators.